Mysterious west - Williams, Brad; Pepper, Choral (World Pub Co., Cleveland, 1967)
In this Western Americana collection "the authors recount tales of sudden and unexplained deaths, of buried treasures and lost missions, of haunted houses and ghost towns, of notorious females and bloodthirsty bandits ... and many other equally bewildering happenings."
35157
Keywords: Southwest; Legends -- West (U.S.); Curiosities and wonders